(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2023)
Purpose: Personal income tax (PIT) and social security contributions (SSC) play a significant role in tax systems. Since both of them affect employers and employees, it is important to analyse the labour costs paid by the employer (gross wage) and the net wage received by the employee, i.e., the tax wedge. Methodology: Following OECD’s Taxing Wages methodology, this paper analyses the characteristics of the tax wedge and the tax wedge policy in the Republic of Croatia and the Republic of Slovenia in the period from 2005 to 2020. Results: The conducted analysis has shown that a Slovenian taxpayer faces the highest average net tax wedge for each observed family type, and that the Croatian tax wedge is lower in all hypothetical units observed. The taxpayer with the highest average gross wage also faces the highest tax burden. The problem of a relatively high tax wedge in Croatia and Slovenia does not lie with the personal income tax, which is relatively low, but with social contributions. Conclusion: The tax wedge primarily depends on the level of income, it decreases if the taxpayer has (more) children, and its amount depends on various levels of tax, deductions and social security contributions. In the future, the focus will be on alleviating the labour tax burden. However, this begs the question of how to further alleviate the burden on labour without implementing major structural reforms in the pension and healthcare system and/or introducing new tax forms.